Rotifer (microzooplankton) production through NPK fertilization - Sharma, O P; Saini, V P (Indian Journal of Fisheries, 2011)
The young stages (spawn) of fish prefer small feed, particularly rotifers. Encouraging results of zooplankton production by using NPK mixture for pond fertilization have been obtained in different parts of the world (Tenner I960;.Prowse 1967, Rabanall967). The present investigation was carried out with locally available NPK mixture having ratio of 18:18:10. Special emphasis was to obtain higher population of rotifers under local environmental conditions.